Measurement of the branching ratio Γ(Λ 0 b → ψ(2S)Λ 0 )/Γ(Λ 0 b → J/ψΛ 0 ) with the ATLAS detector - Aad, G. (2015)
An observation of the Λ 0 b → ψ(2S )Λ 0 decay and a comparison of its branching fraction with that of the Λ 0 b → J/ψΛ 0 decay has been made with the ATLAS detector in proton–proton collisions at √ s = 8 TeV at the LHC using an integrated luminosity of 20.6 fb−1 . The J/ψ and ψ(2S ) mesons are reconstructed in their decays to a muon pair, while the Λ 0 → pπ − decay is exploited for the Λ 0 baryon reconstruction. The Λ 0 b baryons are reconstructed with transverse momentum pT > 10 GeV and pseudorapidity |η| < 2.1. The measured branching ratio of the Λ 0 b → ψ(2S )Λ 0 and Λ 0 b → J/ψΛ 0 decays is Γ(Λ 0 b → ψ(2S )Λ 0 )/Γ(Λ 0 b → J/ψΛ 0 ) = 0.501 ± 0.033(stat) ± 0.019(syst), lower than the expectation from the covariant quark model